Exploring metabolism in scleroderma reveals opportunities for pharmacological intervention for therapy in fibrosis - Cantanhede, Isabella Gomes; Liu, Huan; Liu, Huan; Balbuena Rodriguez, Vestaen; Shiwen, Xu; Ong, Voo H.; Denton, Christopher P.; Ponticos, Markella; Xiong, Guo; Lima-Filho, José Luiz; Abraham, David; Abu-Hanna, Jeries; et al. (Frontiers in Immunology, 2022)
Background Recent evidence has indicated that alterations in energy metabolism play a critical role in the pathogenesis of fibrotic diseases. Studies have suggested that ‘metabolic reprogramming’ involving the glycolysis and oxidative phosphorylation (OXPHOS) in cells lead to an enhanced generation of energy and biosynthesis. The aim of this study was to assess the molecular basis of changes in fibrotic metabolism in systemic sclerosis (Scleroderma; SSc) and highlight the most appropriate targets for anti-fibrotic therapies. Materials and methods Dermal fibroblasts were isolated from five SSc patients and five healthy donors. Cells were cultured in medium with/without TGF-β1 and with/without ALK5, pan-PIM or ATM kinase inhibitors. Extracellular flux analyses were performed to evaluate glycolytic and mitochondrial respiratory function. The mitochondrial network in TMRM-stained cells was visualized by confocal laser-scanning microscopy, followed by semi-automatic analysis on the ImageJ platform. Protein expression of ECM and fibroblast components, glycolytic enzymes, subunits of the five OXPHOS complexes, and dynamin-related GTPases and receptors involved in mitochondrial fission/fusion were assessed by western blotting. Results Enhanced mitochondrial respiration coupled to ATP production was observed in SSc fibroblasts at the expense of spare respiratory capacity. Although no difference was found in glycolysis when comparing SSc with healthy control fibroblasts, levels of phophofructokinase-1 isoform PFKM were significantly lower in SSc fibroblasts (P<0.05). Our results suggest that the number of respirasomes is decreased in the SSc mitochondria; however, the organelles formed a hyperfused network, which is thought to increase mitochondrial ATP production through complementation. The increased mitochondrial fusion correlated with a change in expression levels of regulators of mitochondrial morphology, including decreased levels of DRP1, increased levels of MIEF2 and changes in OPA1 isoform ratios. TGF-β1 treatment strongly stimulated glycolysis and mitochondrial respiration and induced the expression of fibrotic markers. The pan-PIM kinase inhibitor had no effect, whereas both ALK5 and ATM kinase inhibition abrogated TGF-β1-mediated fibroblast activation, and upregulation of glycolysis and respiration. Conclusions Our data provide evidence for a novel mechanism(s) by which SSc fibroblasts exhibit altered metabolic programs and highlight changes in respiration and dysregulated mitochondrial morphology and function, which can be selectively targeted by small molecule kinase inhibitors.